Coherence and Compromise: European Green Deal and European Integration - Jiang, Sijia (Université d'Ottawa | University of Ottawa, 2024)
The European Green Deal (EGD) is a critical initiative in the European Union’s response to climate change, as well as internal challenges in EU as in its deficiencies in energy structure optimization, supportive policies developments and cross-department collaboration. However, member states exhibit divergent attitudes on advocating the policy package influenced by factors such as energy endowment, political motivations, and socioeconomic considerations. The EU must demonstrate its capability to navigate diverse interests and foster collective action by building on coherence through coordination mechanisms and supportive plans. A successful implementation of the EGD requires the collaboration of member states and stakeholders across various levels, whose coherence in return further contributes to European integration. Integration, in this stance, is both a means and an outcome of the mutually constructive interaction. Although uncertainties and challenges persist, including opposition from conservative entities and upcoming elections across Europe, the EU remains committed to prioritizing environmental sustainability, leveraging its historical engagement in environmental policymaking, and fostering collaboration among member states. Moving forward, the EU needs more rigorous efforts to stay on track with its ambitious schedule, thereby continuing to lead the way towards a greener and more sustainable future for Europe and the world. Key words: European Green Deal, European Integration, Climate Change, European Union, Green Transition